GHG inventories and drivers & barriers to climate action : an analysis of Brazilian cities - Leão, Eduardo Baltar de Souza (2021)
Cities are considered core of the global climate change mitigation and strategic low-carbon development and city-level study is a trend for climate change responses studies. The literature review identified three gaps that guided this research: (I) There is lack of consistent and comparable greenhouse gas (GHG) emissions data at the city level; (II) it is necessary to analyze enabling factors that lead to effective urban climate governance and (III) there is a geographical bias of empirical climate governance studies focused on cities from Global North and developed countries realities. To address these gaps, considering the reality of Global South, this thesis had the general objectives of to analyze (I) the quality and gaps of GHG inventories and (II) the main drivers and barriers to climate agenda strengthening in Brazilian cities. Four manuscripts were developed to reach this objective. The first analyzed the differences among the main existing GHG accounting methodologies for cities and identified gaps in carbon inventories of twenty-four Brazilian cities. The second paper compared GHG emissions results of forty-seven Brazilian cities, applying different GHG accounting methodologies. It highlighted characteristics, similarities, and differences of these methodologies, showing how they can impact GHG results. The third and fourth articles discussed about the climate agenda advance in the city of Recife in Brazil. The third paper is a city profile which discusses how geographical characteristics and the historical urbanization process of the city have contributed to the climate risks and vulnerabilities. It evidences factors that can decisively assist cities to strength the climate agenda, mainly in developing or less developed countries. The fourth paper is a case study which discusses the climate actions adopted in Recife and it examines the main drivers and barriers to their effective implementation, comparing to examples from literature. The main important findings are: (I) There are two main types of GHG reporting gaps: incompleteness and lack of transparency which hinder the accuracy, assessment of results and comparability between cities; (II) to analyze GHG reports and to compare results, it is essential to identify methodology, base year, emission sources included, global warming potential, and calculation methods, information which are not transparent in several reports; (III) the drivers to climate action identified include having committed leadership, being part of a multinational network of cities and multilevel governance which supports existing theory, as well as identified climate risks, much in contrast to other European cases; (IV) It is fundamental to institutionalize the climate agenda in the local government to avoid political interferences, which was considered a primary barrier. The thesis provides insights for academics and policymakers on how develop broader, completer, and more transparent GHG inventories and it evidences precautions that should be taken when analyzing a city GHG report. It also evidences factors that can decisively assist cities to strength the climate agenda, mainly in developing or less developed countries, providing insights to academics and policymakers on low carbon strategies for cities. Moreover, it suggests steps that can assist cities to adopt climate actions, particularly in developing or less developed countries.